From Divine Revelation to Legal Practice: Contextualizing Islamic Law in the Contemporary Era - Karimullah, Suud Sarim (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2025)
This study aims to illuminate the gap between the idealism of Islamic law and its practical implementation by providing a deep insight into the associated challenges and potential solutions. The focus is on detailing the obstacles and strategies for realizing a dynamic Islamic law that aligns with the demands of contemporary Muslim societies. Employing library research methods, this study conducts an integrative and comprehensive analysis of the literature, summarizes significant information, traces ongoing debates, and formulates well-rounded conclusions. The findings reveal that the pragmatic application of Islamic law requires an inclusive and open approach to universal values and social contexts. Contextual interpretation and an in-depth understanding of Islamic legal texts are crucial for developing implementation strategies relevant to everyday life, considering social, cultural, political, and technological dynamics. Flexibility and responsiveness in interpreting Islamic law are essential to maintaining its relevance and benefits for the Muslim community. Therefore, Muslim countries must adopt a dynamic approach, remain open to change, and focus on the needs of modern Muslim societies. By integrating universal values that correspond with contemporary times, the implementation of Islamic law transcends legal aspects and becomes a vehicle to promote justice and welfare within Muslim communities today.